Altered lignin biosynthesis using biotechnology to improve lignocellulosic biofuel feedstocks. Issue 9 (22nd July 2014) - Poovaiah, Charleson R.; Nageswara‐Rao, Madhugiri; Soneji, Jaya R.; Baxter, Holly L.; Stewart, Charles N.
Summary Lignocellulosic feedstocks can be converted to biofuels, which can conceivably replace a large fraction of fossil fuels currently used for transformation. However, lignin, a prominent constituent of secondary cell walls, is an impediment to the conversion of cell walls to fuel: the recalcitrance problem. Biomass pretreatment for removing lignin is the most expensive step in the production of lignocellulosic biofuels. Even though we have learned a great deal about the biosynthesis of lignin, we do not fully understand its role in plant biology, which is needed for the rational design of engineered cell walls for lignocellulosic feedstocks. This review will recapitulate our knowledge of lignin biosynthesis and discuss how lignin has been modified and the consequences for the host plant.